Consumer selection of vegetarian food in restaurants - Rosala, Heidi (2015)
Development, which began from agricultural and industrial revolutions has improved and eased human lives on this planet. But the massive growth of the human population has caused some serious environmental impacts on our planet. Millions of hectares of forests have been converted into arable land, fresh water resources are decreasing and oceans are getting overfished, while the demand for food continues to grow. Agriculture is the most important contributor to the climate change and global meat production sector causes more greenhouse gases to the atmosphere than transport. By reducing the consumption of meat and increasing the proportion of vegetables in human diets, the environmental impact of food consumption can be significantly reduced. This research examines how we could motivate consumers into more vegetarian diets and decrease the consumption of meat. Public catering seems to have an important role in contributing healthy eating habits among Finnish people, but the role of individual restaurants, media and the western culture in promoting the sustainable consumption should not be underestimated. This study was made by using mixed methods and performing a consumer research in four Finnish lunch restaurants. The findings of this study indicate that Finnish consumers have a positive attitude towards vegetarian food. The most important factors that motivate consumers to eat more vegetarian food are the good taste, selection, and the health benefits of vegetarian food.